1982
DOI: 10.1002/clc.4960050803
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption in adult patients during cardiac catheterization

Abstract: Summary:The determination of cardiac output by the Fick principle requires the quantitation of the arteriovenous oxygen (02) content difference across the pulmonary bed and the 0 2 consumption. Since a correct measurement of 0 2 consumption may be difficult, an assumed value is sometimes substituted into this equation. Despite this practice, there is no appropriate reference standard for 0 2 consumption applicable to the adult catheterization laboratory. Therefore, we determined 0 2 consumption in 108 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
1
42
0
1
Order By: Relevance
“…Estimated resting VȮ 2 was calculated by the formula of Dehmer, et al 7,9 : VȮ 2 (ml/min) = 125 (ml/min/m 2 ) × body surface area (BSA, m 2 ), with BSA calculated according to the formula of Dubois 13 : BSA (m 2 ) = 0.007184 × Weight (kg) 0.425 × Height (cm) 0.725 . For sensitivity analysis, estimation of VȮ 2 was also calculated using the formula of LaFarge 6 : VȮ 2 (ml/min) = 138.1 -(X × log e age) + (0.378 × Heart Rate) × BSA (Men: X = 11.49; Women: X = 17.04); and the formula of Bergstra 8 : VȮ 2 (ml/min) = 157.3 × BSA + X -(10.5 × log e age) + 4.8 (Men: X = 10; Women = 0).…”
Section: Calculating Estimated Vȯmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated resting VȮ 2 was calculated by the formula of Dehmer, et al 7,9 : VȮ 2 (ml/min) = 125 (ml/min/m 2 ) × body surface area (BSA, m 2 ), with BSA calculated according to the formula of Dubois 13 : BSA (m 2 ) = 0.007184 × Weight (kg) 0.425 × Height (cm) 0.725 . For sensitivity analysis, estimation of VȮ 2 was also calculated using the formula of LaFarge 6 : VȮ 2 (ml/min) = 138.1 -(X × log e age) + (0.378 × Heart Rate) × BSA (Men: X = 11.49; Women: X = 17.04); and the formula of Bergstra 8 : VȮ 2 (ml/min) = 157.3 × BSA + X -(10.5 × log e age) + 4.8 (Men: X = 10; Women = 0).…”
Section: Calculating Estimated Vȯmentioning
confidence: 99%
“…As a result, resting VȮ 2 is commonly estimated rather than measured using derived formulae available in the peer-reviewed literature. [6][7][8][9] However, the accuracy of the formulae and nomograms most commonly used to estimate resting VȮ 2 is questionable, with most estimating methods derived from limited samples of highly selected, ethnically homogenous populations consisting of similarly aged, lean adults, [10][11][12] populations that differ substantially from contemporary adult cardiology practice. Other formulae were derived from clinical populations composed exclusively or primarily of infants and children.…”
mentioning
confidence: 99%
“…Another cause of falsely elevated PCWP in a mechanically ventilated patient is the monitoring catheter being located outside zone 3 (during positive pressure ventilation less of the lung is zone 3 due to elevated alveolar pressures). Care should be taken to demonstrate catheter tip placement within zone 3, gravitationally below the level of the left atrium [64]. Hemodynamic pressure measurements should reflect the time of most neutral intrathoracic pressure (in spontaneously respiring patients this occurs at end expiration, with converse in patients utilizing positive pressure ventilation), rather than sole recording of mean pressure.…”
Section: Right Heart Catheterization In a Mechanically Ventilated Patmentioning
confidence: 99%
“…Several formulas for estimating VO 2 have been developed. 16,17 All have shown variable reliability, [21][22][23] and none have been validated in an elderly cohort. Thermodilution is an alternative method of measuring cardiac output, 24 which makes no assumptions for age, but it has proven unreliable at both low outputs 25 and at high ones.…”
Section: Comparison Of Invasive Techniquesmentioning
confidence: 99%
“…When considering sensitivity and specificity of invasive and noninvasive techniques, we used echocardiography as the reference standard, because this technique is the most widely used. Limitations of cardiac catheterization include the use of mild conscious sedation, which may depress cardiac output, 21 and the use of a catheter across the aortic valve, which may increase the measured gradient. 30 All invasive assessments were based on the assumption that measured VO 2 with the Fick equation is the most accurate, yet even this technique may have the potential for error, depending on the collection method and patient state, 31 and we found that thermodilution correlated better with noninvasive assessment.…”
Section: Study Limitationsmentioning
confidence: 99%